Crop wild relative checklist and inventory descriptors v.1 - Bioversity International; University of Birmingham (Bioversity International, 2017)
The present list of descriptors for the standardized development of crop wild relative (CWR) checklists and inventories is based on results from a series of international projects that progressively worked to improve information management related to CWR conservation and use. The creation of checklists and inventories of crop wild relative are the first steps towards the development of a national strategy and action plan for CWR. This descriptor list aims to facilitate the compilation of these lists in a standardized way.